Practical training programme - Zamula, O. V.; Sitak, I. L.; Prokhorenko, O. V.; Yatsenko, O. M. (National Technical University "Kharkiv Polytechnic Institute", 2026)
The practical training programme is developed for students studying in programs of specialty D3 "Management", first (Bachelor’s) level of higher education. The guideline describes the content of the Practical training, the topics of individual tasks, the requirements for the Practical training report, and also define the main provisions regarding the Practice organizing. Recommended for students of specialty D3 "Management" of all forms of study.
Keywords: practical training programme; management; educational process; teaching activities; students